Policy change and environmental governance at the U.S.-Mexico border: the creation and development of the Border Environment Cooperation Commission/North American Development Bank - Ibáñez Hernández, Oscar Fidencio, author; Mumme, Stephen P., advisor (Colorado State University. Libraries, 2008)
The present research performs a detailed analysis of bilateral environmental policy change using Historical Institutionalism, Punctuated Equilibrium and Policy Regime Theory to explain the origins and evolution of the Border Environmental Cooperation Commission (BECC) and the North American Development Bank (NADB). A multi-level governance approach is used to evaluate the complex interactions of BECC/NADB with several other institutional arrangements and their contribution to the United States-Mexico border environmental governance. The outcomes of the research identify opportunities and provide useful lessons to enhance bi-national environmental and non-environmental cooperation and governance particularly along the countries' common border.
Keywords: Border Environment Cooperation Commission; border infrastructure; environment; governance; international cooperation; Mexico; Mexico-United States; North American Development Bank; United States-Mexico; international law; environmental science; urban planning; public policy